Omega-3 Supplementation Improves Pancreatic Islet Redox Status: In Vivo and In Vitro Studies. Issue 2 (March 2015) - Lucena, Camila F.; Roma, Leticia P.; Graciano, Maria Fernanda R.; Veras, Katherine; Simões, Daniel; Curi, Rui; Carpinelli, Angelo R.
Abstract : Objectives: The aim of the study was to evaluate the potential changes induced by fish oil (FO) supplementation on the redox status of pancreatic islets from healthy rats. To test whether these effects were due to eicosapentaenoic acid and docosahexaenoic acid (ω-3), in vitro experiments were performed. Methods: Rats were supplemented with FO, and pancreatic islets were obtained. Islets were also treated in vitro with palmitate (P) or eicosapentaenoic acid + docosahexaenoic acid (ω-3). Insulin secretion (GSIS), glucose oxidation, protein expression, and superoxide content were analyzed. Results: The FO group showed a reduction in superoxide content. Moreover, FO reduced the expression of NAD(P)H oxidase subunits and increased superoxide dismutase, without altering β-cell function. Palmitate increased β-cell reactive oxygen species (ROS) production, apoptosis, and impaired GSIS. Under these conditions, ω-3 triggered a parallel reduction in ROS production and β-cell apoptosis induced by P and protected against the impairment in GSIS. There was no difference in mitochondrial ROS production. Conclusions: Our results show that ω-3 protect pancreatic islets from alterations induced by P. In vivo FO supplementation modulates the redox state of pancreatic β-cell. Considering that in vitro effects do not involve mitochondrial superoxide production, we can speculate that this protection might involve NAD(P)H oxidase activity.